Solving Problems with The Percentage Bar - Galen, Frans van; Eerde, Dolly van (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2013)
At the end of primary school all children more of less know what a percentage is, but yet they often struggle with percentage problems. This article describes a study in which students of 13 and 14 years old were given a written test with percentage problems and a week later were interviewed about the way they solved some of these problems. In a teaching experiment the students were then taught the use of the percentage bar. Although the teaching experiment was very short - just one lessonÃ‚Â -Ã‚Â the results confirm that the percentage bar is a powerful model that deserves a central place in the teaching of percentages.